Pengaruh struktur kepemilikan terhadap kinerja perusahaan manufaktur yang terdaftar di bursa efek Indonesia - Neneng Wahida; Rahmiati Rahmiati; Yolandafitri Zulvia (Jurnal Kajian Manajemen dan Wirausaha, 2020)
The purpose of this study is to examine the effect of ownership structure on the firm performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX).  This research is a causative study. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange for the period 2013-2018. This study uses secondary data published in the Indonesian Stock Exchange (IDX). Based on data collection, a sample of 75 companies from 144 listed manufacturing companies was obtained. The analytical method used is Multiple Regression using SPSS 24 data processing applications. The results of this study conclude (1) Family Ownership does not have a significant positive effect on firm performance (2) Managerial Ownership has a significant negative effect on firm performance (3) Institutional Ownership has a significant positive effect on firm performance (4) Foreign ownership does not have a significant positive effect on firm performance.  Keywords: Ownership structure, firm performance, Indonesia Stock Exchange.